LDA Topic Analysis for Product Reviews in Social Media Platform - Alzami, Farrikh; Megantara, Rama Aria; Prabowo, Dwi Puji; Sulistiyawati, Puri; Pramunendar, Ricardus Anggi; Dewi, Ika Novita; Ritzkal, Ritzkal (Universitas Ibn Khladun Bogor, 2023)
Social media in recent years is used as platform for product reviews and customer feedback. Thus, to understand the topic which have been discussed, we utilized Latent Dirichlet Allocation for topic modeling. The topic modeling is important due to it can gain insights into the specific features that customers like or dislike about a particular product. Thus, by not using stop words due it have possibilities remove the time domain, the information can be valuable for businesses as it helps them understand customer preferences and inform product development and marketing strategies with the coherence score 0.621520, the topic modeling obtained 3 optimal topics, where the topic 0 discussed about price and time it will be available to purchase. In topic 1 it discussed about the product is hard to obtain due to it not available in market. In topic 2, it discussed about ownership (what they like after usage).